The Role of Peers in Character Formation in Junior High Schools - Warda Aulia Shofa; Puan Damar Swasti (Konsultan Jurnal Ilmiah Indonesia, 2025)
Character development is essential during adolescence, especially in junior high school foefore the sake of preparing a morally upright young generation and foster positive values such as discipline, tolerance, cooperation, and solidarity. Peer friends play a crucial role in children’s character development because social interactions between peers are frequent. This research that conducted using Systematic Literature Learning (SLR) method, aims to identify the role of peer friends in children’s character development especially during adolescence in junior high school. Based on the result of article research using Publish or Perished, linked to Google Scholar, we identified five relevant articles to use it for reference in this study. Based on the presented discussion, it can be concluded that peers take a role as a social agents and provide social, moral, and emotional support for adolescence during their character development period. Peer interactions involving cooperation and problem-solving activities will train adolescence to develop a positive attitudes and character. However, if the interaction that occurs in adolescence are in the form of inappropiate activities oftenly, it will cause the potential of shaping a negative character on student. Thus, the role of peers in developing student’s character is very influential, both in providing negative and positive influences that can support or hinder the development of student’s character.